Seeing, Touching, Holding, and Swallowing Tibetan Buddhist Texts. Issue 1 (3rd July 2017) - Cantwell, Cathy
Abstract : The iconic dimension of holy books has drawn increasing scholarly attention in recent years (e.g. Iconic Books and Texts, James Watts, ed., London, Equinox, 2013). Asian Buddhism provides rich material for considering the ritualization of engagement with sacred texts. In Tibetan Buddhism, this aspect of book culture is perhaps especially pronounced (see, for instance, Schaeffer 2009, especially Chapter 6; Elliott, Diemberger and Clemente 2014). This paper explores the topic in relation to the engagement of the senses in Tibetan context, through seeing, touching, holding and tasting texts. It would seem that it is not the sensory experience in itself, but rather the physical experience of a transmission and incorporation of the sacred qualities from the books into the person which is emphasized in these practices. Parallels and contrasts with examples from elsewhere are mentioned, and there is some consideration of the breadth of the category of sacred books in the Tibetan context in which Dharma teachings may take many forms.